TINGKAT KEPERCAYAAN PASIEN TERHADAP KEAMANAN UNIT PENDAFTARAN RAWAT JALAN DI MASA PANDEMI COVID-19 DI RUMAH SAKIT IMC BINTARO - Hudiyati Agustini; Nurul Ulfa (MEDICORDHIF Jurnal Rekam Medis, 2022)
This study was conducted to obtain an overview of the patient's level of trust in safety in the outpatient registration unit of IMC Bintaro hospital during the COVID-19 pandemic. The number of patients visiting IMC Bintaro Hospital decreased at the beginning of the pandemic, there where 55,101 people who registered outpatients in January-July 2019 while in January-July 2020 only 37,121 people (decreased 32%). This condition is thought to be due to the patient's concern about the transmission of COVID-19. The level of confidence research was carried out using a descriptive method in the outpatient registration unit of the IMC Bintaro Hospital, in February-April 2021. A randomly selected sample of 100 patients where registered in December 2020-February 2021. The technique of collecting data was by interviewing the head of the registration unit, observation, and an electronic questionnaire containing 10 questions related to the patient's level of confidence. The results showed that IMC Bintaro Hospital does not yet have an SOP for outpatient registration adapted to the pandemic conditions. However, health workers and registration areas have implemented health protection based on the Director's memo. While data from questionnaires to patients showed a high level of patient knowledge about COVID-19 (an average of 94.8% answered agree), accompanied by a high level of patient confidence in safety in the outpatient registration unit (an average of 88% answered agree). Most of the samples gave a positive response, they have received services in line with expectations. Patients feel safe for treatment at the IMC Bintaro Hospital during the COVID-19 pandemic. However, it should be understood that the sample was taken from patients who came to the hospital after the pandemic lasted for about 1 year, while number of patients who visited the hospital during the study was not carried out. Keywords: Level of trust, security. COVID-19 pandemic, registration unit